Regulation of the Ukrainian labor market in the context of European integration: system priorities - Risnyy, Oleh (Managerial Economics, 2020)
The purpose of the study is to research the effective international practice of European integration and identify the main system priorities of an effective transformation of the state policy of labor market regulation for Ukraine. The research methods are a comparative analysis concerning the activity of the employment services, the labor market situation in Ukraine and abroad, in particular in Eastern Europe, a statistical analysis of the structure of the employment level, of annual earnings etc., and a systemic analysis, aimed to improve the direction of labor market regulation.